BUDIDAYA SAYURAN ORGANIK MENGGUNAKAN WADAH PADA PEKARANGAN RUMAH MASYARAKAT DI KELURAHAN LATERI KOTA AMBON - Yuliana Wattimena, Anna; Makaruku, Marlita Herlin; Tanasale, Vilma Laurien; Goo, Nureny (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
The yard is an open land that can be used by each household to cultivate vegetables. Organic vegetable cultivation using containers was carried out by a group of housewives RT 006 RW 001 Lateri village by utilizing yard land. The problem faced by housewives is the lack of activities of mothers to grow and develop insight and experience. Mothers' knowledge of the function of open land is limited. The purpose of community service is to provide motivation to utilize the yard into a productive yard by using simple containers for green open yards. The stages carried out in this activity include: preparation activities, training activities including pre-test, counseling, practice, post test and evaluation. The results obtained from community service activities are that participants understand how to make organic fertilizers for vegetable cultivation, multifunctional yards, natural materials around the yard that can be used in making natural pesticides. The level of knowledge of trainees for organic vegetable cultivation using containers provides positive results as well as producing products that can be sold for household economics